Development of a population of digital brain phantoms for radionuclide imaging research in Parkinson’s disease - Wenbo Huang; Han Jiang; Guang-Uei Hung; Yonghua Zhao; Ruibing Wang; Greta S. P. Mok (EJNMMI Physics)
Abstract Purpose Dopamine transporter (DAT) SPECT is a powerful tool for early diagnosis of Parkinson’s disease (PD), while digital phantoms and Monte Carlo (MC) simulations can serve as important research tools. This study aims to develop a novel digital brain phantom population for 99mTc-TRODAT-1 (99mTc) and 123I-ioflupane (123I) brain SPECT, and to assess attenuation correction (AC) and scatter correction (SC) in DAT SPECT. Methods Striatum, brain background (gray and white matter), and cold regions (skull and cerebrospinal fluid) were segmented from 200 T1 MRI brain images from the PPMI dataset. Striatal binding ratio (SBR) values were retrospectively collected from 200 123I and 100 99mTc DAT SPECT patients with suspected PD symptoms from PPMI and a local hospital, respectively. Various activity values were assigned to the randomly paired segmented regions according to a range of SBR values based on the SPECT Visual Interpretation (VI) assessment scheme. The new phantom population was combined with MC simulation tool SIMIND to generate realistic noisy projections. Quantitative accuracy of reconstructed images with attenuation correction (AC) and scatter correction (SC) was assessed. Results A population of 1000 normal and abnormal PD phantoms was generated for both tracers. Visual comparisons and quantitative analyses demonstrated that simulated data exhibited high similarity to clinical data. Reconstructed images with AC + SC achieved the best quantitative results, followed by AC only, without AC and SC, and SC only. Conclusion The developed digital DAT SPECT phantom population can be served for a wide range of PD applications. Attenuation impacts image quality the most in DAT SPECT, while AC + SC is effective to enhance image quality and quantitative accuracy of DAT SPECT.